MATERIAL LOGISTICS RESERVATION PROCEDURE USING SAP AT PT PLN (PERSERO) UP3 LHOKSEUMAWE - Rahmah Mutia; Laiya Putri; M. Al Fasha; Alika Zuhra; Intan Cahyani Rachman; Rahmi Raihan,; Yulianisah Yulianisah (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2024)
This study aims to explain the logistics material reservation procedure implemented at PT PLN (Persero) UP3 Lhokseumawe using the SAP (System Application and Product in Data Processing) system. In its operational process, PT PLN (Persero) requires an efficient and integrated system to support the smooth distribution of logistics materials, especially to support the maintenance and construction of the electricity network. SAP as an Enterprise Resource Planning (ERP) system is used to request, manage, and record materials in a structured and real-time manner, starting from submissions by user units to approval by the Warehouse section through the SAP MM (Material Management) module. The research method used is descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the implementation of the SAP system at PT PLN (Persero) UP3 Lhokseumawe can improve the efficiency of logistics management and reduce the potential for errors in the material request and distribution process. This research is expected to be a reference in the development of logistics information systems in public service-based companies.